2009
DOI: 10.1016/s1472-6483(10)60266-0
|View full text |Cite
|
Sign up to set email alerts
|

GnRH antagonists and endometrial receptivity in oocyte recipients: a prospective randomized trial

Abstract: The effect that gonadotrophin-releasing hormone (GnRH) antagonists exert on endometrial receptivity has not yet been elucidated. GnRH antagonists might directly affect oocytes, the embryo and/or the endometrium. The aim of this study was to investigate the direct effect of GnRH antagonists on the endometrium in oocyte donation cycles. In an oocyte donation programme, oocytes from each donor (n = 49), stimulated with gonadotrophins and a GnRH antagonist, were equally shared between two different matched recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The low implantation and pregnancy rate may be due to the effect of supraphysiological serum estradiol concentrations and GnRH antagonist administration on endometrial receptivity. 21 , 22 So that, when the peak E2 level per oocyte exceed 400 pg/mL, patients should avoid fresh embryo transfer and all embryos should be cryopreserved for frozen-thawed embryos transfer. The peak E2 level/oocyte less than 100 pg/mL indicates that the oocytes are immature.…”
Section: Discussionmentioning
confidence: 99%
“…The low implantation and pregnancy rate may be due to the effect of supraphysiological serum estradiol concentrations and GnRH antagonist administration on endometrial receptivity. 21 , 22 So that, when the peak E2 level per oocyte exceed 400 pg/mL, patients should avoid fresh embryo transfer and all embryos should be cryopreserved for frozen-thawed embryos transfer. The peak E2 level/oocyte less than 100 pg/mL indicates that the oocytes are immature.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent study, Prapas et al [20] studied the effects of GnRH antagonists on endometrial receptivity in oocyte donation cycles. Their study showed that use of antagonists in dose of 0.25 mg per day did not effect either the endometrial development or the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Higher pregnancy rates were also shown in a gonadotropin intrauterine insemination cycle than in a cycle where no intervention took place [57]. In a prospective randomized trial, Prapas et al [58] reported that GnRH antagonist administration during the proliferative phase did not adversely affect endometrial receptivity in oocyte recipients.…”
Section: Introductionmentioning
confidence: 99%